Pd(II)-Catalyzed Enantioselective C-H Olefination of Diphenylacetic Acids - Shi, Bing-Feng (2010)
[Image: see text] Pd(II)-catalyzed enantioselective C-H olefination of diphenylacetic acid substrates has been achieved through the use of mono-protected chiral amino acid ligands. The absolute configuration of the resulting olefinated products is consistent with that of a proposed C-H insertion intermediate.